Bioequivalence Study of 100 mcg Levothyroxine Sodium Tablets in Patients Who Have Hypothyroidism with Euthyroid in Steady State - Chattanachotikul, Weerathep (Siriraj Medical Journal, 2015)
Objective: The purpose of this study was to ascertain the bioequivalence between a test product (100 mcg levothyroxine sodium tablets; Thyrosit, SRIPRASIT PHARMA Co., Ltd., Thailand) and the reference product (100 mcg anhydrous thyroxine sodium; Eltroxin, GlaxoSmithKline). Methods: An open-label, 2-treatment, 2-period, 2-sequence, randomized crossover design without washout period was studied in 16 patients (8 females in group 1, 1 male and 7 females in group 2) who were diagnosed hypothyroidism with euthyroid in steady state. The enrolled subjects were given a tablet of 100 mcg levothyroxine sodium either the test or reference product daily for 57 days of each period. At steady state (Day 57 on period 1 and Day 114 on period 2), blood samples were collected over a 24-h interval and the concentrations of T4 were examined by a Microparticle Enzyme Immunoassay technique. Pharmacokinetic parameters were evaluated from plasma concentration-time profiles of T4 using the non-compartmental analysis without the adjustment of baseline levels. Results: The 90% confidence interval of geometric mean ratio of primary target parameters(Cssmax and AUC0-24(ss)) between the test and reference formulations was entirely within the bioequivalence acceptance limits of 80.00-125.00%, which was 103.32% (97.99-108.93%) for Cssmax ratios, and 102.32% (96.97-107.96%) for AUC0-24(ss) ratios, together with the power more than 80%. In addition, the nonparametric Friedman’stest for Tssmax demonstrated no significant difference between the two formulations (p>0.05). All subjects tolerated their medication well. No serious adverse effect was observed. Conclusion: The test and reference products of thyroxine in this study are bioequivalent and well tolerated. Keywords: Levothyroxine, hypothyroidism, bioequivalence